Mrhapharli Thakali Samaj - Aryal, Sabitri (Tribhuvan University Journal, 2010)
Not available. Key words: Thakali Samaj; Thakkhola; Mustang; Nepal Tribhuvan University Journal Volume XVI, 1993 Page:108-113 Uploaded date: 4 October, 2010